2015
DOI: 10.1097/ico.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy and Cut-Failure Rates of Eye Bank-Cut Corneas for Use in Endothelial Keratoplasty

Abstract: From 2010 to 2013, the combined cut-failure rates trended toward improvement, while the accuracy of graft thickness improved. This study suggests that the accuracy and success rates of tissue preparation for endothelial keratoplasty improve with experience and volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a previous study using data from 1501 corneas cut at SightLife, Inc, in 2013, the tissue wastage rate was 4.5% in corneas with anterior scars (including post-refractive surgery) compared to 1.36% in healthy corneas devoid of pathology. 28 In the current study using data from the same eye bank, but including over 10 000 corneas encompassing the years 2012-2016 (higher failure rates earlier on), the tissue wastage rates were similar: 5.0% in the post-LASIK/PRK group compared to 2.2% in the control group. Similar analyses have been performed using smaller datasets: 4.4% (5 failures in 113 attempts on post-refractive surgery donor tissue) compared to 1.6% (72 failures in 4519 attempts on nonpost-refractive surgery corneas) at the Lions Vision Gift Eye Bank (Portland, Oregon, USA) from 2009 to 2012; and 1.5% (1 failure in 66 attempts on post-refractive surgery donor tissue) compared to 2.8% (17 failures in 600 attempts on non-post-refractive surgery corneas) at the John A. Moran Eye Center (surgeon cut).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In a previous study using data from 1501 corneas cut at SightLife, Inc, in 2013, the tissue wastage rate was 4.5% in corneas with anterior scars (including post-refractive surgery) compared to 1.36% in healthy corneas devoid of pathology. 28 In the current study using data from the same eye bank, but including over 10 000 corneas encompassing the years 2012-2016 (higher failure rates earlier on), the tissue wastage rates were similar: 5.0% in the post-LASIK/PRK group compared to 2.2% in the control group. Similar analyses have been performed using smaller datasets: 4.4% (5 failures in 113 attempts on post-refractive surgery donor tissue) compared to 1.6% (72 failures in 4519 attempts on nonpost-refractive surgery corneas) at the Lions Vision Gift Eye Bank (Portland, Oregon, USA) from 2009 to 2012; and 1.5% (1 failure in 66 attempts on post-refractive surgery donor tissue) compared to 2.8% (17 failures in 600 attempts on non-post-refractive surgery corneas) at the John A. Moran Eye Center (surgeon cut).…”
Section: Discussionmentioning
confidence: 59%
“…[9][10][11][12][13][14][15][16] Previous analyses on the accuracy (achieving an actual thickness of the lenticule within 20 mm of the desired thickness) and cut failure rates (percentage of tissue that is rendered unusable owing to complications from cutting) of eye bank-cut corneas have mainly concentrated on corneas with no history of refractive procedures. 28,29 However, in the last 20 years there has been an increase in the popularity of refractive procedures, such as laser in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK), and there has been anecdotal evidence, as well as some limited data, suggesting that post-LASIK corneas result in higher complication rates during precutting for DSAEK. 27 Despite successful processing, however, it is unknown whether or not the refractive predictability is as good with these tissues compared with normal corneas: the previous laser ablation may alter the central-toperipheral thickness ratio of the endothelial keratoplasty lenticule, which may in turn result in unanticipated refractive changes.…”
mentioning
confidence: 99%
“…4 Multiple studies have demonstrated comparable tissue quality and positive surgical results from eye bank-prepared corneal tissue for DSEK. 65,68,70,71 In a study evaluating tissue quality of DSEK grafts (n=197), 98% of eye bank-prepared grafts were deemed acceptable for surgery and were not associated with increased risk of complications due to tissue preparation. 65 Terry noted that dislocation rates and postoperative endothelial cell density were also comparable for surgeon versus eye bank-prepared tissue.…”
Section: Descemet Stripping Endothelial Keratoplasty (Dsek)mentioning
confidence: 99%